AN EXISTENCE THEOREM FOR A CLASS OF DIFFERENTIAL INCLUSIONS WITH A PRECISE ESTIMATE ON THE GRADIENT OF A SOLUTION - Mir, S.; Ghaemi, M. B.; Afrouzi, G. A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2014)
In this paper, by using nonsmooth version of very recently theorem of Ricceri relating to continuously functionals, we get a new class of nonlinearities for which the Dirichlet problem has a solution, with a precise estimate on the gradient.